The Cul3 ubiquitin ligase engages Insomniac as an adaptor to impact sleep and synaptic homeostasis. - Qiuling Li; Kayla Y Lim; Raad Altawell; Faith Verderose; Xiling Li; Wanying Dong; Joshua Martinez; Dion Dickman; Nicholas Stavropoulos (PLoS Genetics)
Mutations of the Cullin-3 (Cul3) E3 ubiquitin ligase are associated with autism and schizophrenia, neurological disorders characterized by sleep disturbances and altered synaptic function. Cul3 engages dozens of adaptor proteins to recruit hundreds of substrates for ubiquitination, but the adaptors that impact sleep and synapses remain ill-defined. Here we implicate Insomniac (Inc), a conserved protein required for normal sleep and synaptic homeostasis in Drosophila, as a Cul3 adaptor. Inc binds Cul3 in vivo, and mutations within the N-terminal BTB domain of Inc that weaken Inc-Cul3 associations impair Inc activity, suggesting that Inc function requires binding to the Cul3 complex. Deletion of the conserved C-terminus of Inc does not alter Cul3 binding but abolishes Inc activity in the context of sleep and synaptic homeostasis, indicating that the Inc C-terminus has the properties of a substrate recruitment domain. Mutation of a conserved, disease-associated arginine in the Inc C-terminus also abolishes Inc function, suggesting that this residue is vital for recruiting Inc targets. Inc levels are negatively regulated by Cul3 in neurons, consistent with Inc degradation by autocatalytic ubiquitination, a hallmark of Cullin adaptors. These findings link Inc and Cul3 in vivo and support the notion that Inc-Cul3 complexes are essential for normal sleep and synaptic function. Furthermore, these results indicate that dysregulation of conserved substrates of Inc-Cul3 complexes may contribute to altered sleep and synaptic function in autism and schizophrenia associated with Cul3 mutations.